Arahan Tata Ruang Pengelolaan Hutan Desa Lubuk Beringin Kecamatan Bathin III Ulu Kabupaten Bungo Provinsi Jambi - Achmad, Eva; Fazriyas, Fazriyas; Pratiwi, Hutari Ladjusa (Fakultas Kehutanan Universitas Jambi, 2018)
The research is aimed to provide recommendation on spatial planning of Hutan Desa Lubuk Beringin management. The research was conducted through direct observation, semi-structure interview, visual interpretation and literature review. Based on the interpretation result of Landsat image with acquisition year in 2014, the types of landuse existed over the areas were old jungle rubber, ecotourism potency and environmental services. The analyses for spatial planning of Hutan Desa Lubuk Beringin with the area of 2.602 ha divided by two zones, namely protection zones and utilization zones. The area of Protection zone covered 84% of total area that equal to 2.602 ha. This area has functions to protect the lower areas and to maintain ecological functions contributing the intangible benefits for people around the village forest. Utilization zone has area of 411 ha that equal to 16% of the total area which has been used for mixed garden or old jungle rubber by the villagers. Furthermore, the management of Lubuk Beringin village forest is ruled by the conservation commitment of village (KKD) and managed by the institution called village forest management group (KPHD) Ndendang Hulu Sako Batang Buat.